Pengaruh Kualitas Pelayanan dan Persepsi Harga terhadap Kepuasan dan Minat Berkunjung Kembali pada Wisata Pancur Pitu di Kabupaten Madiun - Budi, Ikhwan Sulistya; Chrismardani, Yustina (Jurnal Kajian Ilmu Manajemen (JKIM), 2025)
The purpose of this study is to (1) To determine the effect of service quality on satisfaction at Pancur Pitu Tourism, (2) To determine the effect of Perceived Price on satisfaction at Pancur Pitu Tourism, (3) To determine the effect of satisfaction on the intention to revisit Pancur Pitu Tourism, (4) To determine the quality of service on the intention to return to Pancur Pitu Tourism, (5) To determine the effect of Perceived Price on the intention to return to Pancur Pitu Tourism, (6) To determine the indirect effect of service quality on the intention to return to Pancur Pitu Tourism, (7) ) To find out the indirect effect of perceived price on the intention to return to Pancur Pitu Tourism. The method used in this study was the quantitative method with a type of confirmatory research. Data collection techniques in this study used a questionnaire. The sample was taken using the infinite formula because the population size is unknown, and the samples will be taken at Pancur Pitu Tourism in 100 samples. The results of this study indicate (1) service quality has a significant effect on satisfaction at Pancur Pitu Tourism Object, (2) perceived price has no significant effect on visitor satisfaction at Pancur Pitu Tourism Object, (3) satisfaction has a significant effect on the intention to return to visitors at Pancur Pitu Tourism Object, (4) service quality has a significant effect on the intention to return to visitors at Pancur Pitu Tourism Object, (5) perceived price has a significant effect on the revisit intention to return to visitors at Pancur Pitu Tourism Object, (6) service quality through satisfaction has a significant effect on the intention to return to visitors at the Pancur Pitu Tourism Object, (7) the perception of price through satisfaction has no significant effect on the intention to return to the visitors at the Pancur Pitu Tourism Object.